Defense in Competition: Multimarket and Structural Effects of Firm-Specific Competition on Risk Transfer - Yu, Jifeng; Lin, Yijia (Journal of Management, 2024)
This study extends current knowledge on competition and corporate defense by investigating how firms transfer risk in response to their firm-specific multimarket and structural competitive conditions. Drawing on the theory of multimarket competition, we propose an inverted U–shaped relationship between multimarket competition and risk transfer. We also propose that, for the sake of gaining a competitive edge, the extent to which a firm manages risk will tend to be opposite to that of its competitors. Last, we propose that egocentric industry concentration will moderate the relationship between multimarket competition and risk transfer besides its direct effect. Analysis of reinsurance usage in the US property and casualty insurance industry strongly supports our model and shows that firm-specific competitive conditions are salient to a firm's risk transfer level.